2016
DOI: 10.1162/jocn_a_00944
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Integration of Contextual Information across Objects

Abstract: Abstract■ Recognizing objects in the environment and understanding our surroundings often depends on context: the presence of other objects and knowledge about their relations with each other. Such contextual information activates a set of medial lobe brain regions, the parahippocampal cortex and the retrosplenial complex. Both regions are more activated by single objects with a unique contextual association than by objects not associated with any specific context. Similarly they are more activated by spatiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…It is involved in memory for visual scene images ( Montaldi et al, 2006 ; Takashima et al, 2006 ; Elman et al, 2013 ; van Assche et al, 2016 ), learning navigational routes ( Burgess et al, 2001 ; Bray et al, 2015 ), and even imagining past events or future events in familiar places ( Hassabis et al, 2007 ; Szpunar et al, 2009 ). It can integrate information across space ( Livne and Bar, 2016 ) and time ( Lerner et al, 2011 ; Vilberg and Rugg, 2012 ), and has been shown in lesion studies to be critical for orientation and navigation ( Kravitz et al, 2011 ). Our connectivity results and meta-analysis suggest that cIPL may play a prominent role in connecting visual scenes to the real-world location they depict.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in memory for visual scene images ( Montaldi et al, 2006 ; Takashima et al, 2006 ; Elman et al, 2013 ; van Assche et al, 2016 ), learning navigational routes ( Burgess et al, 2001 ; Bray et al, 2015 ), and even imagining past events or future events in familiar places ( Hassabis et al, 2007 ; Szpunar et al, 2009 ). It can integrate information across space ( Livne and Bar, 2016 ) and time ( Lerner et al, 2011 ; Vilberg and Rugg, 2012 ), and has been shown in lesion studies to be critical for orientation and navigation ( Kravitz et al, 2011 ). Our connectivity results and meta-analysis suggest that cIPL may play a prominent role in connecting visual scenes to the real-world location they depict.…”
Section: Discussionmentioning
confidence: 99%
“…It also opens the question of the mechanism through which these high-level factors may affect the attentional distribution. Previous research has suggested that an object’s contextual associations are derived in the parahippocampal and retrosplenial cortices (Bar & Aminoff, 2003; Livne & Bar, 2016). These representations could potentially affect the spatially organized attentional priority map in inferior parietal sulcus (IPS, Sheremata & Silver, 2015), either directly, or indirectly by influencing object recognition processing regions in the inferior temporal cortex (Bar, 2004), before influencing activity in IPS.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in memory for visual scene images (Montaldi et al, 2006;Takashima et al, 2006;Elman et al, 2013;van Assche et al, 2016), learning navigational routes (Burgess et al, 2001;Bray et al, 2015), and even imagining past events or future events in familiar places (Hassabis et al, 2007;Szpunar et al, 2009). It can integrate information across space (Livne and Bar, 2016) and time (Lerner et al, 2011;Vilberg and Rugg, 2012), and has been shown in lesion studies to be critical for orientation and navigation (Kravitz et al, 2011). Our connectivity results and metaanalysis suggest that cIPL may play a prominent role in connecting visual scenes to the real-world location they depict.…”
Section: The Memory and Navigation Networkmentioning
confidence: 99%